2007
DOI: 10.1002/jcb.21149
|View full text |Cite
|
Sign up to set email alerts
|

A delicate balance: TGF‐β and the tumor microenvironment

Abstract: The activated form of TGF-beta is a known regulator of epithelial cell autonomous tumor initiation, progression, and metastasis. Recent studies have also indicated that TGF-beta mediates interactions between cancer cells and their local tumor microenvironment. Specifically, the loss of TGF-beta signaling in stromal components including fibroblasts and T-cells can result in an "activated" microenvironment that supports and even initiates transformation of adjacent epithelial cells. TGF-beta signaling in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 43 publications
1
111
0
4
Order By: Relevance
“…Using a mouse model for SMO-mediated BCC development, we identified changes in several signaling pathways, particularly TGF␤ signaling. TGF␤ signaling is a known pathway important for tumor development (10,11). Using two biological assays as well as one BCC mouse model, we demonstrated the critical role of TGF␤ signaling in SMO-mediated signaling and cancer development.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Using a mouse model for SMO-mediated BCC development, we identified changes in several signaling pathways, particularly TGF␤ signaling. TGF␤ signaling is a known pathway important for tumor development (10,11). Using two biological assays as well as one BCC mouse model, we demonstrated the critical role of TGF␤ signaling in SMO-mediated signaling and cancer development.…”
Section: Discussionmentioning
confidence: 89%
“…TGF␤ signaling is a known pathway important for tumor development. Depending on the stage of tumor development and cellular context, TGF␤ signaling can function as tumor suppressor, tumor promoter, or modulator for immune surveillance and inflammation (10,11). We investigated the significance of TGF␤ signaling for SMO-mediated signaling.…”
mentioning
confidence: 99%
“…This concept is best illustrated in the cancer literature. Depending on the combination effects of multiple factors in the tumor microenvironment (eg, the presence of other growth factors), immune cell population dynamics, and ECM composition, TGF-␤ could either promote or suppress cancer progression and metastasis 53,56,57 by altering the proliferative responses in the same cell line. In a previous study, 8 we observed that TGF-␤ expression is up-regulated on mechanical wounding and that, in response to injury, exog- enous TGF-␤ promotes VIC proliferation while it inhibits apoptosis in the early stage of wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…Activated JNK and NFkB in turn induce gene expression of proinvasive factors such as EMMPRIN (extracellular matrix metallo-protease inducer) and MIF (migration inhibitory factor), whose expression enhances MMP-2 and -9 secretion and activity (Hagemann et al 2005). Production of TGFb by alternatively activated macrophages in mammary tumors, mesenchymal support cells, and immature myeloid cells (IMCs) can also enhance the invasive and metastatic programming of malignant cells (Stover et al 2007;Bierie et al 2008;Yang et al 2008) consistent with existence of a TGFb-responsive gene signature that a predicts breast cancer pulmonary metastasis (Arribas et al 1997).…”
Section: Leukocytes In Mammary Development and Cancermentioning
confidence: 99%